2007
DOI: 10.1242/jcs.007369
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene disruption of dynein heavy chain 7 ofTetrahymena thermophilaresults in altered ciliary waveform and reduced swim speed

Abstract: SummaryTargeted gene disruption of dynein heavy chain 7 of Tetrahymena thermophila results in altered ciliary waveform and reduced swim speed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…Our results show that loss of ccp5 induces hyperglutamylation in zebrafish pronephric cilia and reduces cilia beat coordination and beat amplitude without affecting beat frequency. This may reflect a preferential effect of hyperglutamylation on inner dynein arm activity, consistent with previously reported effects of TTLL deficiency on axonemal microtubule sliding and the role of inner dynein arms in regulating cilia waveform (Brokaw and Kamiya, 1987; Wood et al. , 2007; Suryavanshi et al.…”
Section: Discussionsupporting
confidence: 90%
“…Our results show that loss of ccp5 induces hyperglutamylation in zebrafish pronephric cilia and reduces cilia beat coordination and beat amplitude without affecting beat frequency. This may reflect a preferential effect of hyperglutamylation on inner dynein arm activity, consistent with previously reported effects of TTLL deficiency on axonemal microtubule sliding and the role of inner dynein arms in regulating cilia waveform (Brokaw and Kamiya, 1987; Wood et al. , 2007; Suryavanshi et al.…”
Section: Discussionsupporting
confidence: 90%
“…In the spermatozoa from mice lacking the inner arm dynein heavy chain 7 (DyHC7) gene, the lateral amplitude of the flagella beat is decreased by 50% compared with controls, resulting in reduced swimming velocities of spermatozoa, but their CBF was unaffected [28]. In Tetrahymena, DyHC6-or 7-knockout mutants show an irregular ciliary beat waveform, a normal CBF, and decreased swim speeds [19][20][21]. Thus, the results of this study are consistent with those previously reported in PCD patients, mice and Tetrahymena with inner arm dynein defects: that is, that an increase in CBA is the key factor controlling the rate of ciliary transport.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice that lack the inner arm dynein heavy chain 7 gene (DyHC7), spermatozoa flagella show an abnormal beating waveform and a decreased lateral amplitude but have a normal CBF. Chlamydomonas and Tetrahymena mutants lacking DyHC7 also show an irregular ciliary waveform pattern, decreased CBA, slower swim speed, but they still have a normal CBF [19,21,22]. These observations suggest that CBA is of particular importance for regulating the mucociliary transport rate in airways.…”
Section: Introductionmentioning
confidence: 89%
“…The doublet is very stable and robust. It does not break under significant stress during rapid ciliary/flagellar beating with a frequency range of between ∼16 to 70 Hz1314. The outstanding stability of the doublet is likely linked to microtubule inner proteins (MIPs), which bind firmly to the inner wall of the doublet microtubule101115.…”
mentioning
confidence: 99%